Diverting young offenders from crime in Ireland: the need for more checks and balances on the exercise of police discretion - Smyth, Philip (2011)
"The Irish police (the Garda Síochána) have been exercising their law enforcement discretion to pursue a diversionary strategy for young offenders since at least 1953. Working in a street environment of low visibility they have managed to expand their traditional law enforcement function into territory more appropriately reserved for courts, social workers and probation officers. This article charts the development of this expansion and examines its current manifestation in the juvenile diversion programme. It argues that the welfare benefits for the young offenders are being purchased at the cost of due process rights, and that there is a need for more custom built accountability checks and balances to strike a better balance in the programme." [auhtor's abstract]